2010
DOI: 10.1677/joe-10-0243
|View full text |Cite
|
Sign up to set email alerts
|

Hexosamines stimulate apoptosis by altering SIRT1 action and levels in rodent pancreatic  -cells

Abstract: The activity and levels of SIRT1, which promotes cell survival in several models, are linked to glucose concentrations and cellular energy metabolism. The present study aimed to determine whether impaired Sirt1 activity is involved in the induction of apoptosis by the nutrientsensing hexosamine biosynthesis pathway (HBP). Pancreatic Nit-1, Rin-m5F, and Min6 b-cells were acutely treated at different doses and times with glucosamine, which enters and stimulates the HBP. Sirt1 levels were genetically modulated by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 50 publications
1
12
0
Order By: Relevance
“…Thus, HSP attenuates unresolved inflammation (Newsholme & de Bittencourt 2014). Amino acids, such as L-glutamine, are required for the optimal HSP70 response, through the HBP-induced activation of SIRT1/HUR (Lafontaine-Lacasse et al 2011, which was observed in our study (Fig. 5A and C respectively).…”
Section: Discussionsupporting
confidence: 74%
“…Thus, HSP attenuates unresolved inflammation (Newsholme & de Bittencourt 2014). Amino acids, such as L-glutamine, are required for the optimal HSP70 response, through the HBP-induced activation of SIRT1/HUR (Lafontaine-Lacasse et al 2011, which was observed in our study (Fig. 5A and C respectively).…”
Section: Discussionsupporting
confidence: 74%
“…Despite the fact that HSF1 can bind in the heat shock elements (HSEs) in the nuclei, promoting HSP expression (e.g., HSP72) its activation may occur by other mechanisms, such Sirtuin 1 (SIRT1)/HuR modulation (Gabai et al, 2012). SIRT1/HuR are mostly modulated by severe inflammation, oxidative stress situations, and nutrients (Kim et al, 2012;Lafontaine-Lacasse et al, 2011;Newsholme et al, 2014). Therefore, increased expression of HSF1, with or without HSP70 stimulation may improve the inflammation status, increasing the liver's ability to respond under harmful situations (e.g., chronic inflammation).…”
Section: Discussionmentioning
confidence: 99%
“…SIRT1 is susceptible to intracellular fluctuations in the NAD + -to-NADH ratio and may influence type 2 diabetes risk by its known epigenetic effects and β-cell apoptosis (4,7,8). Recently, Sandovici et al (9) showed that suboptimal nutrition in rats during early development led to epigenetic silencing and reduced the expression of the transcription factor Hnf4a, which is required for pancreatic β-cell differentiation and glucose homeostasis.…”
Section: Discussionmentioning
confidence: 99%